Molecular Epidemiology of Porcine Circovirus Type 2 and Porcine Parvoviruses in Guangxi Autonomous Region, China - Pin Chen; Geng Wang; Jiping Chen; Weichao Zhang; Yin He; Ping Qian (Microbiology Research, 2023)
Both porcine circovirus (PCV) and porcine parvovirus (PPV) cause various diseases and bring huge economic losses to the global swine industry. PCV2 is associated with several diseases and syndromes, including postweaning multisystemic wasting syndrome (PMWS), porcine dermatitis and nephropathy syndrome (PDNS) and porcine respiratory disease complex (PRDC). The classical PPV is one of the most common causes of reproductive failure in pigs. In this study, tissue samples (tonsil, lung, mesenteric lymph node, hilar lymph node and superficial inguinal lymph node) were collected from pigs with suspected PCV2-associated disease (PCVAD), and viral DNA was extracted. The coinfection of PCV2 and PPV1–5 was detected using the polymerase chain reaction (PCR) method. Phylogenetic analysis based on capsid genes of PCV2, PPV2, PPV3 and PPV5 was conducted. The prevalence rates of PCV2, PPV1, PPV2, PPV3, PPV4 and PPV5 were 51.2%, 15.9%, 36.6%, 19.5%, 14.6% and 10.9% on the individual pig level, respectively. The coinfection rates of PCV2 with PPV1, PPV2, PPV3, PPV4 and PPV5 were 8.5%, 25.6%, 17.1%, 13.4% and 3.7%, respectively. The prevalence of PPV2, PPV3 and PPV4 in PCV2-positive pigs was significantly higher than those in PCV2-negative pigs. Phylogenetic analyses were performed using the neighbor-joining (NJ) method with 1000 bootstraps. The results indicated the existence of PCV2d and two major clusters of PPV2, PPV3 and PPV5 in the Guangxi Autonomous Region. PCV2d was the dominant strain, and the novel PPVs were circulating in domestic pigs in the Guangxi Autonomous Region. The results of this study underline the importance of active surveillance of PCV2d and PPVs from the swine population in this area.